Konseling Kelompok Dengan Teknik Psikodrama Untuk Mengurangi Perilaku Agresif Peserta Didik di MA Hidayatul Insan Palangkaraya - Naily Arifah; Heru Nurrohman (Suluh: Jurnal Bimbingan dan Konseling, 2017)
The purpose of this study was to determine the group counseling services with psychodrama techniques can reduce the aggressive behavior of students in class XII IPA at MA Hidayatul Insan. Popu; asi in this study were 25 students. The sample population of this study consisted of 8 students. Sampling is determined by purposive sampling technique. Data collection techniques use observation, interviews, and scale of aggressive behavior. The method used is the Equivalent Time Series Design Experiment. Analysis of the data used in this study using the Wilcoxom test formula, namely by comparing the results of the pre-test and post-test with the help table to test Wilcoxom. The calculation used is comparing the smallest level of the pre test and post test with the table of critical prices in the Wilcoxom test. Based on the results of the analysis and discussion above, it can be concluded that the group counseling services with psychodrama techniques can reduce aggressive behavior in students of class XII IPA MA Hidayatul Palangkaraya Insan. This is based on the results of the test conducted by Wilcoxom, showing that aggressive behavior decreased by an average of 54.63 to 22.25, with an average number of decreases of 32.